Qualitative tests for the determination of fraud in raw milk: evaluation of the influence of analytical parameters of the tests and the stability of the samples as a function of time and preservation form (Research, Society and Development, 2021)
The present work aimed to evaluate the robustness of qualitative tests of frauds of addition of chlorine/hypochlorite, hydrogen peroxide and starch in raw milk, which parameters have the greatest influence on these analytical methods, and to evaluate the influence of time and mode of preservation of intentionally adulterated samples. The effects of the variation of some parameters of the analytical procedures were evaluated, making combinations between the different factors, determining the degree of influence of these variations on the tests. The stability time of the frauds in the samples was evaluated, keeping them under refrigeration (3±2 °C) and carrying out the tests on the same day, and under freezing (≤ -18 °C) for 5, 9 and 15 days, later analyzed, verifying if the frauds were detected. According to the results, it could be observed that the chlorine/hypochlorite detection method was adequate, detecting the addition of the adulterant in all combinations of variables and in all forms of conservation of the samples. The method for detecting the addition of hydrogen peroxide proved to be adequate for the samples analyzed immediately (< 24 h), detecting the presence of the substance in all combinations. However, the method did not detect the presence of peroxide in the combinations for the frozen samples, indicating that the method can generate false negatives in samples that are not fresh. The starch detection method did not detect the presence of this contaminant in all combinations of variables. The combinations that used only a drop of the Lugol’s iodine solution showed false negatives, so the amount of added solution is a critical variable for the method. However, for the other combinations, the method proved to be adequate for both fresh and frozen samples, detecting the addition of starch, regardless of storage time.